To find the hypotenuse the formula would be:
c^2 = a^2 + b^2
BUT! These two questions ask for the length of the smaller sides, so we need to rearrange the formula to:
a^2 = c^2 - b^2
Where c is the hypotenuse, and b is the other known length. Use this formula to solve the length of the unknown side.
Let's call the unknown side x,
1) a^2 = c^2 - b^2
x^2 = 17^2 - 15^2
x^2 = 64
Square root both sides to get x
x = 8
2) a^2 = c^2 - b^2
x^2 = 26^2 - 24^2
x^2 = 100
Square root both sides to get x
x = 10
Hope this helped! Ask me if there's any part of the working you don't understand :)